The aggregate degradation characteristics of stone mastic asphalt (SMA) mixtures - Mohd. Akhir, Norliza (2006)
Stone Mastic Asphalt (SMA) mixtures are designed to have a high coarse aggregate content and stone-on-stone contact which results in more stress on the coarse aggregate particles during compaction and traffic loads. For that reason, aggregates tend to break down more in SMA mixtures than in conventional densegraded mixtures. Aggregate degradation during compaction and traffic loading may cause changes in the original gradation and thus may also affect the volumetric parameters of SMA mixtures. The main objective of this study was to determine the degree of aggregates degradation in SMA mixtures due to compaction process. Aggregates with two Nominal Maximum Aggregates Size (NMAS) which designated as SMA14 and SMA20 were compacted using the effort of 50 blows of Marshall Hammer and 100 gyrations of Superpave Gyratory Compactor (SGC). The verified samples were then prepared and extracted using Centrifuge Method. The same procedure was also performed for the cored samples. The comparisons of gradation of cored samples with the laboratory samples were evaluated to examine the aggregate degradation with respect to different compaction efforts. The relationship between aggregate degradation and influencing factor such as compaction efforts, and volumetric properties were investigated. Aggregate degradation by the Marshall Hammer was found to be significantly higher than degradation by the SGC. Voids in mineral aggregate (VMA) of either compaction methods decrease or almost the same when aggregate degradation is not significant. SGC methods can be selected to represent the field roller that result in similar trend of aggregate degradation.